How do you find the roots, real and imaginary, of y= x^2 - 12x-1 using the quadratic formula?
3 Answers
See a solution process below:
Explanation:
To find the roots we solve
For
Substituting:
The solutions are
Explanation:
The quadratic equation is
Our equation is
Start by calculating the discriminant
As,
The roots are
So,
This quadratic has zeros
Explanation:
Note that:
x^2-12x-1
is in the standard form
ax^2+bx+c
with
This has zeros given by the quadratic formula:
x = (-b+-sqrt(b^2-4ac))/(2a)
color(white)(x) = (-(color(blue)(-12))+-sqrt((color(blue)(-12))^2-4(color(blue)(1))(color(blue)(-1))))/(2(color(blue)(1))
color(white)(x) = (12+-sqrt(144+4))/2
color(white)(x) = (12+-sqrt(148))/2
color(white)(x) = (12+-sqrt(2^2*37))/2
color(white)(x) = (12+-2sqrt(37))/2
color(white)(x) = 6+-sqrt(37)
Bonus
Since
Define:
{ (a_0 = 0), (a_1 = 1), (a_(n+2) = 12a_(n+1)+a_n " for " n >= 0) :}
Note that the recurrence rule is chosen such that the sequence:
1, x, x^2
satisfies it if and only if
Since
The first few terms of this sequence are:
0, 1, 12, 145, 1752, 21169, 255780
Then:
6 + sqrt(37) ~~ 255780/21169 ~~ 12.082762530
which is correct to
Incidentally, since
6 - sqrt(37) = -1/(6+sqrt(37)) ~~ -21169/255780 ~~ -0.08276253030
which is correct to